Legacy effects of individual crops affect N2O emissions accounting within crop rotations. Issue 2 (8th July 2017) - Adler, Paul R.; Spatari, Sabrina; D'Ottone, Federico; Vazquez, Daniel; Peterson, Lisa; Del Grosso, Stephen J.; Baethgen, Walter E.; Parton, William J.
Abstract: Uruguay is pursuing renewable energy production pathways using feedstocks from its agricultural sector to supply transportation fuels, among them ethanol produced from commercial technologies that use sweet and grain sorghum. However, the environmental performance of the fuel is not known. We investigate the life cycle environmental and cost performance of these two major agricultural crops used to produce ethanol that have begun commercial production and are poised to grow to meet national energy targets for replacing gasoline. Using both attributional and consequential life cycle assessment (LCA) frameworks for system boundaries to quantify the carbon intensity, and engineering cost analysis to estimate the unit production cost of ethanol from grain and sweet sorghum, we determined abatement costs. We found 1) an accounting error in estimating N2 O emissions for a specific crop in multiple crop rotations when using Intergovernmental Panel on Climate Change(IPCC) Tier 1 methods within an attributional LCA framework, due to N legacy effects; 2) choice of baseline and crop identity in multiple crop rotations evaluated within the consequential LCA framework both affect the global warming intensity (GWI) of ethanol; and 3) although abatement costs for ethanol from grain sorghum are positive and from sweet sorghum they are negative, both grain and sweet sorghum pathways have a high potential for reducing transport fuel GWI by more than 50% relative to gasoline, and are within the ranges targeted by the US renewable transportation fuel policies. Abstract : We found 1) an accounting error in estimating N2 O emissions for a specific crop in multiple crop rotations when using IPCC Tier 1 methods within an attributional LCA framework, due to N legacy effects; 2) choice of baseline and crop identity in multiple crop rotations evaluated within the consequential LCA framework both affect the global warming intensity (GWI) of ethanol; and 3) although abatement costs for ethanol from grain sorghum are positive and from sweet sorghum they are negative, both grain and sweet sorghum pathways have high potential for reducing transport fuel GWI by more than 50% relative to gasoline.